gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Reductions in exposures to simulated respiratory aerosols by a ceiling-mounted HEPA air filtration unit - William G. Lindsley; Raymond C. Derk; Jayme P. Coyle; Francoise M. Blachere; Theresa Boots; Stephen B. Martin; Kenneth R. Mead; John D. Noti (Building and Environment, 2025)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Relationship between in feed drugs, antibiotics and organic enrichment in marine sediments at Canadian Atlantic salmon aquaculture sites - M.V. Kingsbury; D. Hamoutene; P. Kraska; A. Lacoursière-Roussel; F. Page; T. Coyle; T. Sutherland; O. Gibb; C.W. Mckindsey; F. Hartog; S. Neil; K. Chernoff; et al. (Marine Pollution Bulletin, 2023)

Whole-tree dormant season nitrogen pools for different species receiving combinations of fertilization and irrigation after one short rotation - Gabriel W.D. Ferreira; Mark D. Coleman; David R. Coyle; Doug P. Aubrey (Forest Ecology and Management, 2023)

Efficacy of Do-It-Yourself air filtration units in reducing exposure to simulated respiratory aerosols - Raymond C. Derk; Jayme P. Coyle; William G. Lindsley; Francoise M. Blachere; Angela R. Lemons; Samantha K. Service; Stephen B. Martin; Kenneth R. Mead; Steven A. Fotta; Jeffrey S. Reynolds; Walter G. McKinney; Erik W. Sinsel; et al. (Building and Environment, 2023)

Invited review: human air-liquid-interface organotypic airway tissue models derived from primary tracheobronchial epithelial cells—overview and perspectives - Xuefei Cao; Jayme P. Coyle; Rui Xiong; Yiying Wang; Robert H. Heflich; Baiping Ren; William M. Gwinn; Patrick Hayden; Liying Rojanasakul (In Vitro Cellular & Developmental Biology - Animal, 2021)

A first worldwide multispecies survey of invasive Mediterranean pine bark beetles (Coleoptera: Curculionidae, Scolytinae) - Massimo Faccoli; Diego Gallego; Manuela Branco; Eckehard G. Brockerhoff; Juan Corley; David R. Coyle; Brett P. Hurley; Hervé Jactel; Ferenc Lakatos; Victoria Lantschner; Simon Lawson; Gonzalo Martínez; et al. (Biological Invasions, 2020)

Acrolein Can Cause Cardiovascular Disease: A Review - Robert J. Henning; Giffe T. Johnson; Jayme P. Coyle; Raymond D. Harbison (Cardiovascular Toxicology, 2017)

Detection of phosphate transporter genes from arbuscular mycorrhizal fungi in mature tree roots under experimental soil pH manipulation - Sarah R. Carrino-Kyker; Laurel A. Kluber; Kaitlin P. Coyle; David J. Burke (Symbiosis, 2017)

Mycoplasma hominis and Gardnerella vaginalis display a significant synergistic relationship in bacterial vaginosis - C. Cox; A. P. Watt; J. P. McKenna; P. V. Coyle (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Genetic basis of continuous variation in the levels and modular inheritance of pigmentation in cichlid fishes - R. Craig Albertson; Kara E. Powder; Yinan Hu; Kaitlin P. Coyle; Reade B. Roberts; Kevin J. Parsons (Molecular Ecology, 2014)
Variation in pigmentation type and levels is a hallmark of myriad evolutionary radiations, and biologists have long been fascinated by the factors that promote and maintain variation in coloration across populations. Here, we provide insights into the genetic basis of complex and continuous patterns of colour variation in cichlid fishes, which offer a vast diversity of pigmentation patterns that have evolved in response to both natural and sexual selection. Specifically, we crossed two divergent cichlid species to generate an F 2 mapping population that exhibited extensive variation in pigmentation levels and patterns. Our experimental design is robust in that it combines traditional quantitative trait locus ( QTL ) analysis with population genomics, which has allowed us to move efficiently from QTL interval to candidate gene. In total, we detected 41 QTL and 13 epistatic interactions that underlie melanocyte‐ and xanthophore‐based coloration across the fins and flanks of these fishes. We also identified 2 QTL and 1 interaction for variation in the magnitude of integration among these colour traits. This finding in particular is notable as there are marked differences both within and between species with respect to the complexity of pigmentation patterns. While certain individuals are characterized by more uniform ‘integrated’ colour patterns, others exhibit many more degrees of freedom with respect to the distribution of colour ‘modules’ across the fins and flank. Our data reveal, for the first time, a genetic basis for this difference. Finally, we implicate pax3a as a mediator of continuous variation in the levels of xanthophore‐based colour along the cichlid flank.

A comparison of the efficiency of ELISA and selected primer sets to detect Norovirus isolates in southern Ireland over a four-year period (2002-2006): variation in detection rates and evidence for continuing predominance of NoV GII.4 genotype - G. Lennon; N. Reidy; P. J. Collins; L. Gunn; P. V. Coyle; B. Cryan; S. Fanning; H. O’Shea (Archives of Virology, 2014)

Hydraulic limitation on maximum height of Pinus strobus trees in northern Minnesota, USA - Mark R. Fulton; John C. Kamman; Matthew P. Coyle (Trees, 2014)

Functional groups show distinct differences in nitrogen cycling during early stand development: implications for forest management - Doug P. Aubrey; David R. Coyle; Mark D. Coleman (Plant and Soil, 2012)

Lack of effect of sublingual salvinorin A, a naturally occurring kappa opioid, in humans: a placebo-controlled trial - John E. Mendelson; Jeremy R. Coyle; Juan Carlos Lopez; Matthew J. Baggott; Keith Flower; E. Thomas Everhart; Thomas A. Munro; Gantt P. Galloway; Bruce M. Cohen (Psychopharmacology, 2011)

Ice Damage in Loblolly Pine: Understanding the Factors That Influence Susceptibility - Doug P. Aubrey; Mark D. Coleman; David R. Coyle (Forest Science, 2007)
Winter ice storms frequently occur in the southeastern United States and can severely damage softwood plantations. In January 2004, a severe storm deposited approximately 2 cm of ice on an intensively managed 4-year-old loblolly pine (Pinus taeda L.) plantation in South Carolina. Existing irrigation and fertilization treatments presented an opportunity to examine the effects of resource amendments on initial ice damage and subsequent recovery. Fertilized treatments showed more individual stem breakage, whereas nonfertilized treatments showed more stem bending; however, the proportion of undamaged trees did not differ between treatments. Irrigation did not influence the type of damage. Trees that experienced breakage during the storm were taller with larger diameter and taper and leaf, branch, and crown biomass compared with unbroken trees. One growing season after ice damage, relative height increases were significantly greater for trees experiencing stem breakage compared with unbroken trees; however, relative diameter increases were significantly lower for these trees. Relative diameter increases for broken trees were smaller for fertilized treatments compared with nonfertilized treatments. A reduction in wood strength was ruled out as the cause of greater breakage in fertilized trees; rather, fertilized trees had reached an intermediate diameter range known to be susceptible to breakage under ice loading.

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Human metapneumovirus in adults: a short case series - C. O’Gorman; E. McHenry; P. V. Coyle (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Changes in plasma zinc, copper, iron, and hepatic metallothionein in adjuvant-induced arthritis treated with cyclosporin - A. M. Rofe; J. C. Philcox; D. R. Haynes; M. W. Whitehouse; P. Coyle (Biological Trace Element Research, 1992)

Two anti-parvovirus B 19 IgM capture assays incorporating a mouse monoclonal antibody specific for B 19 viral capsid proteins VP 1 and VP 2 - H. J. O'Neill; P. V. Coyle (Archives of Virology, 1992)